ANALYSIS OF GRAM-NEGATIVE BACTERIA IN COMMON-USE BATHROOMS OF A HIGHER EDUCATION INSTITUTION IN TERESINA-PI (REMUNOM, 2025)
Public restrooms in higher education institutions are environments prone to microbiological contamination due to the intense flow of people, high humidity, and frequent contact with high-touch surfaces such as faucets and sinks. The presence of Gram-negative bacteria in these areas poses a significant public health risk, given their intrinsic resistance to various antimicrobials and their potential to cause opportunistic infections. Therefore, this study aimed to evaluate the presence and prevalence of Gram-negative bacteria in restrooms at a higher education institution in Teresina, Piauí. This experimental study involved collecting samples from surfaces in different restrooms within the institution. After bacterial isolation on specific culture media, the colonies were subjected to MALDI-TOF mass spectrometry analysis for microbiological identification. The results were organized according to frequency of occurrence and characterization of the isolated species. All samples showed bacterial growth, confirming the widespread contamination of external surfaces. Acinetobacter baumannii predominated, isolated in 26 samples, followed by Enterobacter sp. and Pseudomonas aeruginosa, both detected in eight samples. The persistence of these species reflects their high intrinsic resistance to antimicrobials, as well as flaws in hygiene and ventilation protocols, which favor colonization in humid environments. The identified bacterial diversity, combined with the multidrug-resistant profile, suggests the need for more rigorous biosafety measures. Therefore, shared restrooms represent significant reservoirs of Gram-negative bacteria with potential health risks. These results reinforce the importance of intensifying cleaning protocols, implementing continuous microbiological monitoring, and promoting health education, ensuring a reduction in indirect transmission through surfaces and greater protection for the academic community.